AJIC Issue 29, 2022 - Full Issue - (:unkn) unknown (My University, 2022)
Articles on digital vaccination records; defining decentralisation in permissionless blockchain systems; copyright flexibilities for combatting COVID-19; value creation and socioeconomic inclusion in maker communities; public-speaking anxiety among novice university instructors; and interactions between primary school teachers and parents during COVID-19.